"A serious rift": The Indigenous Health Research Community's Refusal of the 2014 CIHR Funding Reforms and Underlying Methodological Conservatism - Rose, John; Castleden, Heather (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2022)
In 2014, the Canadian Institutes of Health Research (CIHR) senior administration established reforms to the Open Suite of Programs and Peer Review processes (OSP), implementing changes that it claimed would improve its funding and peer review structures. The purpose of the research reported in this paper was to investigate how CIHR reforms to the OSP were poised to negatively affect Indigenous health research. We found that the reforms were guided by a governmental and institutional trajectory of methodological conservatism that (a) privileged commercial research over projects that focus on social determinants of health and community relations, and (b) created a peer review system re-designed in ways that reduce inclusiveness. Interventions by the CIHR Institute of Indigenous Peoples Health' Advisory Board and an ad-hoc Indigenous Health Research Steering Committee (kahwa:tsire) were urgently organized and mobilized to reverse the CIHR decisions that were being made under the guise of so-called 'consultation.’